Can someone explain to me in detail how to complete these two problems without using truth tables? I'm having a hard time understanding what to do. I know that I'm supposed to use the laws, etc. But I'm confused on where to even start.
Prove that ((p → q) ∧ ¬q) → ¬p is a tautology without using truth tables. Show intermediate steps and mention what law you are using.
Prove that (p → r) ∧ (q → r) is logically equivalent to (p ∨ q) → r using only the logical equivalences. Show intermediate steps and mention what law you are using.
Thanks for any help!! These two links along with the one in my comment, denotes the laws for proving. All of these